Developing the "right" breakthrough product/service: an umbrella methodology - Part A. (1st January 1999) - Noori, Hamid; Munro, Hugh; Deszca, Gene; McWilliams, Brenda
Breakthrough products and services (BTP/S) have been found to contribute significantly to corporate profits and market position. However, because such products are designed to meet needs that may not yet be apparent in the market and have no historical point of reference, traditional market forecasting techniques are unable to provide accurate predictions of market success for them. An alternative to traditional approaches is explored in this research paper. It involves combining forecasts of quantifiable environmental variables with qualitative analysis of uncertainties through scenario creation and investigation. This "umbrella approach" assesses future goals, needs, desires, and product development direction, and works backward to the present to determine what steps must be completed to reach that end state. The process of continuous monitoring allows firms to determine which pathway they are following, and to incorporate current information into their product development processes.